Dissolved and colloidal copper in the tropical South Pacific. (15th July 2018) - Roshan, Saeed; Wu, Jingfeng
Highlights: Dissolved Cu shows enrichment in the deep tropical South Pacific. Dissolved Cu strongly correlates with silicate in the upper 1500 m. A subtle feature in dissolved Cu distribution can be attributed to hydrothermal input. Dissolved Cu physical speciation shows distinct pools of particles/molecules among <5 kDa and >300 kDa. Molecular weight spectrum of dissolved Cu species is uniform at 2200–2800 m along the study region. Abstract: Copper (Cu) as a bioactive trace metal in the ocean has widely been studied in the context of chemical speciation. However, this trace metal is extremely understudied in the context of physical speciation (i.e., size- or molecular weight-partitioning), which may help in characterizing dissolved Cu species. In this study, we determine total dissolved Cu (<0.2 μm) distribution and its physical speciation along the US GEOTRACES 2013 cruise, a 4300-km east-west transect in the tropical South Pacific. The distribution of dissolved Cu is rather uniform horizontally and exhibits a linear increase with depth from surface to 2500–3000 m, below which it varies less significantly both vertically and horizontally. Dissolved Cu shows a strong correlation with silicate (SiO4 4− ) in the upper 1500 m, which is in agreement with previous studies in other regions. This correlation is weaker but with higher slope at depths below 1500 m, which supports the sedimentary source hypothesis. Although hydrothermal activity at the East Pacific Rise (EPR) does not show a readily evident impact on the dissolved Cu distribution, high-quality data at 2300–2800 m allow for diagnosing a subtle westward decrease in the background-subtracted dissolved Cu component. This component of dissolved Cu poorly correlates with mantle-derived 3 He (R 2 = 0.41), indicating a possible hydrothermal source for dissolved Cu, in contrast to previous studies. For the first time in a major basin, we also determined the physical speciation of dissolved Cu, which shows that Cu species lighter than 10 kDa (Da = 1 g mol −1 ) dominate the pool of dissolved Cu (<0.2 μm) below 1000 m with a contribution of 61 ± 6% (fraction of total dissolved). 39 ± 6% of dissolved Cu at depths below 1000 m, thus, occurs in the pool of colloidal matter (10 kDa–0.2 μm). Moreover, using a suite of molecular weight cutoffs indicate that Cu species are distributed between two distinct molecular weight classes: the lighter than 5 kDa and heavier than 300 kDa classes, which form 53 ± 6% and 37 ± 7% of dissolved Cu at 2200–2800 m, respectively. The Cu species with molecular weight between 5 kDa and 300 kDa contribute only to 10 ± 12% of the pool at 2200–2800 m. These results offer new insights into structure, reactivity and bioavailability of oceanic Cu compounds. As an organic-dominating metal, Cu physical speciation may also shed light on size-reactivity spectrum of dissolved organic matter (DOM) in the deep ocean.